Recent Developments of Mn(II)-Doped 2D-Layered and 2D Platelet Perovskite Nanostructures - Das Adhikari, Samrat; Pradhan, Narayan (Frontiers in Materials, 2020)
Two-dimensional (2D) layered perovskites recently emerged as one of the most promising materials for optoelectronics. These not only behave like a quantum well structures, but also on doping Mn(II) ions at the Pb site result as a highly emissive doped material. These structures can also be used as a starting material for obtaining 3D perovskites. Thermal treatment of Mn(II)-incorporated layered perovskites in presence of Cs(I) ions led to Mn(II)-doped 2D platelet–shaped perovskites, which also tune their dimensions with varying dopant ion concentrations. Keeping the importance of the 2D-layered perovskites, this review focused on the basic structures to the recently developed synthetic strategies and their optical properties of layered structured perovskites, Mn(II)-doped layered perovskites, and Mn(II)-doped 2D platelet–shaped perovskites.